Expectations Evoked on Hearing a Piece of Music for the First Time: Evidence from a Musical Savant - Grundy, Ruth; Ockelford, Adam (Empirical Musicology Review, 2014)
This study investigates expectations in music evoked during the course of hearing a piece for the first time, particularly those which stem from recently appearing groups of notes (Ockelford, 2006). A prodigious musical savant (Derek Paravicini) attempted to reproduce a novel composition on the piano at the same time as hearing it. The piece was designed to minimise the impact of the more general expectations that arise from tonality, whereby different pitch transitions are felt to occur with different probabilities according to their level of past exposure. The design of the study was informed by ‘zygonic’ theory (Ockelford, 2009, 2012b), which holds that structural regularities in music suggest future continuations, whose perceived likelihood of occurrence is proportional to the number of ways in which their existence is implied in what has gone before. Using this principle, a ‘strength of implication’ factor was calculated for each note of the stimulus piece (following the first). It was hypothesised that the higher the implication factor, the more likely Derek would predict its occurrence (and therefore play it correctly at the appropriate point in time). Data gathered from Derek’s performance support the principles of the zygonic model, although they also suggest certain refinements.